Comparison of analgesic efficacy of erector spinae plane block at different levels in laparoscopic cholecystectomies: a randomized controlled trial - Serpil Şehirlioğlu; Ümran Yaman; Ayfer Kaya Gök; Ülkü Aygen Türkmen; Döndü Genç Moralar; Muhammed Özdemir (BMC Anesthesiology)
Abstract Background Erector Spinae Plane Block (ESPB) is employed as a component of multimodal analgesia in laparoscopic cholecystectomy (LC) procedures. The objective of this study is to assess the impact of ESPB performed at different levels during LC operations on postoperative pain scores and opioid consumption. Methods A total of 103 patients undergoing LC were divided into three groups: Group Th7 (ESPB administered at the 7th thoracic vertebra level), Group Th9 (ESPB administered at the 9th thoracic vertebra level), and the control group. Patients were evaluated at 30 min, 1, 4, 8, 12, and 24 h postoperatively. Morphine consumption within the first 24 h postoperatively, resting and dynamic Numeric Rating Scale (NRS) scores, and complication rates were assessed. Results When comparing morphine consumption among the groups, it was observed that patients who received ESP blocks had significantly lower morphine consumption at 1, 4, 8, 12, and 24 h compared to the control group. However, no significant difference was found between Group Th7 and Group Th9. In Group Th7 and Group Th9, the resting NRS scores at 30 min, 1, 4, and 24 h, as well as all dynamic NRS scores except at the 8th hour, were significantly lower compared to the control group. However, there was no significant difference between Group Th7 and Group Th9. Conclusion In LC surgeries, ESPB administered at the Th7 and Th9 levels exhibited similar analgesic efficacy. ESPB applied at the Th7 and Th9 levels can be utilized as part of multimodal analgesia.